Peptides Isolated from Yak Milk Residue Exert Antioxidant Effects through Nrf2 Signal Pathway. (31st December 2021) - Yang, Feiyan; He, Xudong; Chen, Tao; Liu, Jinliang; Luo, Zhang; Sun, Shuguo; Qin, Dandan; Huang, Wenyang; Tang, Yiping; Liu, Chunai; Luo, Feijun
Abstract : Food-derived bioactive peptides are considered as the important sources of natural bioactive ingredients. Approximately 3094 peptides were identified by nESI-LC–MS/MS in the hydrolyzed yak milk residue. Peptide KALNEINQF (T10) is the strongest antioxidant peptide. The damage model of H2 O2 -induced human umbilical vein endothelial cells (HUVECs) was used to evaluate the antioxidant effect. After treatment with 25, 50, or 100  μ g/mL T10 peptide, T10 obviously decreased H2 O2 -induced damage and increased the cell survival. Comparing with the H2 O2 -induced damage group, superoxide dismutase (SOD) activities were significantly increased 1.03, 1.1, and 1.33 times, and glutathione reductase (GR) activities were significantly increased 1.11, 1.30, and 1.43 times, respectively. Malondialdehyde (MDA) also reduced 1.41, 1.54, and 1.72 times, respectively. T10 inhibited H2 O2 -induced apoptosis in HUVECs, and protein expressions of the apoptosis-related genes bcl-2 and bax were increased and decreased by 1.95 and 1.44 times, respectively, suggesting T10 decreases apoptosis of the mitochondria-dependent pathway. Comparing with the H2 O2 -induced damage group, the RNA expressions of Nrf2, HO-1, and NQO1 were significantly increased by 2.00, 2.11, and 1.94 times; the protein expressions of p-Nrf2, HO-1, and NQO1 were significantly increased by 2.67, 1.73, and 1.04 times; and Keap1 was downregulated by 3.9 and 1.32 times, respectively. T10 also regulated the Nrf2 pathway and expressions of related genes (Keap1, HO-1, and NQO1), and blocking the Nrf2 pathway in the model decreased the protective effect of T10. Taken together, T10 peptide isolated from yak milk residue has a protective effect against H2 O2 -induced damage in HUVECs and the molecular mechanisms are involved in the regulation of Nrf2 signaling pathway and cell apoptosis.